Use of Box-Behnken design in the preparation of mesoporous carbon coated monolith - BET surface area - Darmadi,; Choong, Thomas Shean Yaw; Chuah, Teong Guan; Yap, Taufiq Yun Hin; Thaib, Anwar (International Congress of Chemistry and Environment, 2011)
Preparation of fiirfuryl alcohol based activated carbon monolith is reported. The effects of the preparation parameters like carbonization temperature, concentration of polyethylene glycol (PEG) and molecular weight of PEG on surface area are investigated. Based on Box-Behnken design, a quadratic model is developed to correlate the preparation parameters to surface area. From the analysis of variance. (ANOVA), carbonization temperature, concentration of polyethylene glycol (PEG) and molecular weight of PEG are identified the dominant parameters in controlling the surface area. The maximum surface area found from the liSM is 58'5.6m'Vg at carbonization temperature of 660°C and concentration of PEG of 31% vol. with molecular weight of PEG of 1000 g/mol.